(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forensic dentistry is the connection between the dental professions and forensic professions. In fact, the teeth and jaws are highly resistant to degradation and decomposition by postmortem. For a number of different reasons and situations such as mass disasters, in criminal investigations and in the case of disfigured bodies due to fire and vehicle accidents, dental identification of humans happens. The different methods include x-rays, antemortem & post-mortem photographs, tooth prints, palatal rugae, lip printing, bite marking and molecular methods such as polymerase chain reaction for pulp DNA analysis.